1982
DOI: 10.22230/cjc.1982v8n2a268
|View full text |Cite
|
Sign up to set email alerts
|

Issue-Specific Agenda-Setting:The Whole as less than the Sum of the Parts

Abstract: The Agenda-Setting hypothesis of mass media effects posits a direct, causal link between the issues and personalities emphasized in the communication media and public salience of those issues and personalities. While this broad statement has been useful for making general assertions to the effect that the media "tell us what to think about," it remains a general statement which must be further delineated (McCombs, 1977).A number of Agenda-Setting researchers have ignored the attempts at theory building in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Issue characteristics have been shown to play a strong role in mediating the traditional media's issue agenda setting effect. Prior research has shown that media's agenda setting impact is stronger with unobtrusive issues or issues that the audience has less direct, personalized experience with in real‐world contexts (Zucker, 1978; Winter, Eyal, & Rogers, 1982; Smith, 1987; Weaver et al, 1981). The media's ability to influence the audience's agenda with issues is also related to the nature of the issue: Abstract issues are more difficult to transfer to the audience than concrete issues (Yagade & Dozier, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Issue characteristics have been shown to play a strong role in mediating the traditional media's issue agenda setting effect. Prior research has shown that media's agenda setting impact is stronger with unobtrusive issues or issues that the audience has less direct, personalized experience with in real‐world contexts (Zucker, 1978; Winter, Eyal, & Rogers, 1982; Smith, 1987; Weaver et al, 1981). The media's ability to influence the audience's agenda with issues is also related to the nature of the issue: Abstract issues are more difficult to transfer to the audience than concrete issues (Yagade & Dozier, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, attention to national unity -which has the highest standard deviation over the period -is characterized by marked punctuations and long lulls (see Figure 1). The salience of national unity is likely driven by some combination of real-world events, media, public opinion, and government priorities (Winter et al 1982;Soroka 2002: 30). As we have seen, within the government, the disproportionate attentiveness given to national unity issues by the BQ suggests that it is overwhelmingly responsible for taking the issue to the House.…”
Section: Variance Of Bq Attentiveness On National Unity With Public Omentioning
confidence: 99%
“…While the terrorist group that staged the kidnappings was essentially undone by these events, Quebec soon saw the rise of a legitimate political party working for sovereignty, and Canada's ensuing national unity crisis remains unresolved. News coverage of these events was heavy, and most of it was classified as national in this study (Soderlund et al ; Winter et al ; Taras ).…”
Section: Discussionmentioning
confidence: 81%